Analysis of solar power generation on California turkey ranches - Palermo, Rick (Kansas State University, 2009)
The objective of this thesis is to conduct a net present value analysis of installing a solar power generation system on company owned turkey grow out ranches. This research project provides information regarding the systems power production capacity, investment cost, maintenance requirements, amount of energy saved, useful life of the equipment, marginal state and federal tax brackets for the company. The investment cost of the system includes the price of the equipment and installation service. Many of the system costs may be offset by rebates, tax credits and grants from various government agencies. These must also be included in the financial analysis as they can greatly affect the financial viability of the project. The system is projected to have a useful life of 30 years with an inverter replacement planned for year 15. Four scenarios were evaluated using two levels of rebates and two electrical rate inflation levels. The evaluations conducted showed positive after tax NPV evaluations on three of four scenarios reviewed with the most financially attractive options available when the rebates, tax credits and grants were maximized. This was the case at both electrical rate inflation scenarios. These same scenarios produced favorable results when looking at reduction of live production ranch costs. The system effectively locked in electrical rates below current rates for the 30 year life of the system. This reduced ranch live production cost by as much as 11.73 percent. It also gives the company an advantage over the competition when used as a marketing tool due to the use of green technology in company production practices.
Keywords: Solar power; Turkeys; California; Electricity; Net Present Value; Agriculture, General (0473); Economics, Agricultural (0503); Energy (0791)